Juan Santos Vara y Ramses A. Wessel (eds.), The Routledge Handbook on the International Dimension of Brexit, Routledge, Londres, 2020, xvi-356 pags. - Martín Rodríguez, Pablo (Revista de Derecho Comunitario Europeo, 2021)
Recensión de la obra señalada